Estrategia de marketing digital y logística para la empresa electro link de la ciudad de Guayaquil periodo 2022 - Bravo González, Kevin Lenin (2023)
This case study is based on digital marketing and logistics and its main objective is to improve the digital shopping experience and logistics in the company Electrolink in the city of Guayaquil and in this way, it seeks to enhance sales and be able to satisfy the customer. client, by identifying the problems that have arisen in the company such as ignorance and little use of digital tools, this has caused a decrease in their sales, it is intended to provide solutions that help improve the warehouse, the approach methodology through techniques and instruments such as interviews and surveys conducted with the owner and customers of Electrolink, preparing question questionnaires that helped to decipher the shortcomings that the company presents to improve its profitability and highlight that company among the competition , so that you can position yourself in the commercial market. With the elaboration of the questionnaire of questions that was made to the owner of the Electrolink company and the surveys applied to the customers of the store, it was confirmed that this company presents a malfunction on the part of the employees within the functions granted by the owner, noting that they have not had the proper advice and practice in the digital marketing strategy and logistics in the application of inventories has not been carried out with correct organization, despite having a large part of the acceptance in the attention and satisfaction towards the clients suggest that the Electrolink company implemented digital marketing strategies for the best performance of its business.